2021
DOI: 10.1155/2021/2643690
|View full text |Cite|
|
Sign up to set email alerts
|

Moving Target Localization in Sports Image Sequence Based on Optimized Particle Filter Hybrid Tracking Algorithm

Abstract: This paper proposes a fusion stadium positioning algorithm, which uses self-optimizing particle filter to integrate the improved athlete dead reckoning and WiFi position fingerprint algorithm for stadium positioning. In order to determine the initial absolute position of the stadium positioning, for athletes entering the stadium from the outside, a seamless switching algorithm outside the stadium is proposed, using the characteristics of high-altitude satellite GPS to find a suitable switching point as the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For a discrete finite set T ={ γ 1 , γ 2 , ..., γ n }, the fuzzy set can be expressed as B ={ γ B ( γ 1 ), γ B ( γ 2 ), ..., γ B ( γ n )} [ 10 ]. In order to better express the concept of the degree of belonging of the domain elements, Zadeh proposed the following form of expression: …”
Section: Point Tracking Of Moving Targets Based On Fuzzy Clustering A...mentioning
confidence: 99%
“…For a discrete finite set T ={ γ 1 , γ 2 , ..., γ n }, the fuzzy set can be expressed as B ={ γ B ( γ 1 ), γ B ( γ 2 ), ..., γ B ( γ n )} [ 10 ]. In order to better express the concept of the degree of belonging of the domain elements, Zadeh proposed the following form of expression: …”
Section: Point Tracking Of Moving Targets Based On Fuzzy Clustering A...mentioning
confidence: 99%
“…rough the above experiments and data analysis, it can be found that the problems to be improved in the badminton court in the gymnasium of the school mainly include insu cient lighting and glare [23][24][25]. Regarding the problem, we will improve the badminton court in the school's gymnasium.…”
Section: Improvement Measures For Badminton Courtmentioning
confidence: 95%
“…The corresponding moving object detection algorithm is now a trend of research [13]. For example, Guo Yan proposed a fusion algorithm for a stadium location, which uses a selfoptimizing particle filter to combine an improved algorithm for athlete trajectory estimation with a Wifi localization fingerprint algorithm to localize the stadium and then achieve object detection through image recognition [14]. Additionally, Luis Ruiz Suarez et al, "proposed a deep learning-based object detection algorithm in remote sensing images, where the image background needs to be distinguished to achieve accurate recognition results in video surveillance [15].…”
Section: Related Workmentioning
confidence: 99%